The Twenty-First Century Hybrid Conflicts - Marsili, M. (Challenges to European Security, 2022)
Alongside non-international and international conflicts, a third category of armed conflict is emerging: hybrid, asymmetric, and transnational conflicts which involve state and non-state actors such as insurgents or terrorist organisations. Unconventional conflicts are among the trend topics of defence and security, and they pose a threat to the stability of international order. States and international organisations, such as the UN and NATO, face difficulty using the tools currently available. International law, in particular International Humanitarian Law and the law of war (Geneva and Hague conventions), is good as long as it deals with conventional conflict, or with civil war within a single country, but it shows its limits when faced with hybrid conflict, e.g.: the Russo-Ukrainian conflict (not officially termed as an armed conflict, but as a “special military operation”); the Nagorno-Karabakh conflict; electromagnetic and cyber conflicts; cognitive and information warfare; terrorism, etc. This paper aims to investigate whether new rules are required to deal with situations of unconventional and hybrid conflict, or if current rules are still valid and can be used/adapted.